Perceived Stress and Anxiety of Healthcare Providers Before and After a Hospital Accreditation Program in Ahvaz City, Iran - Rajab Dashti Kalantar; Marziyeh Asadizaker; Ismail Azizi-Fini; Safoura Yadollahi (Iran University of Medical Sciences, 2023)
Background: Evaluation and accreditation of hospitals have essential roles in improving the quality, safety, and effectiveness of healthcare services. Nevertheless, this process may cause stress and anxiety among hospital staff. This study aims to determine and compare employees' anxiety levels and perceived stress before and after the accreditation program in private hospitals in Ahvaz City, Iran. Methods: This research was a quantitative, observational, and longitudinal study. A total of 456 employees of Ahvaz private hospitals were recruited by convenience sampling. The state-trait anxiety inventory (STAI) and the perceived stress scale-14 (PSS-14) were used to measure the level of anxiety and stress among hospital employees one month before and one month after implementing the hospital accreditation program. The data were analyzed in SPSS software, version 22 using descriptive and inferential statistics, such as the paired t-test, Pearson, and Spearman correlation coefficients. The significance level was set at P<0.05. Results: The findings showed a significant difference between perceived stress and anxiety before and after implementing the accreditation program (P<0.05). There was a significant relationship between the employees' perceived stress levels and their age, gender, and work experience. The subjects' state-trait anxiety was also significantly associated with their sex, work experience, and organizational position (P<0.05). Conclusion: Although the accreditation program usually improves the quality of healthcare, the employees experienced more stress and anxiety before the implementation of this program than after its completion, which can negatively affect the quality of care. Therefore, policymakers and managers should pay great attention to prevent stress and anxiety among healthcare providers while implementing the accreditation program.